Intestinal Duplication Management in Adult Patients: A Systematic Review - Putranto, Agi S.; Siregar, Sun P.; Satrio, Taufik B. (The New Ropanasuri Journal of Surgery, 2018)
Introduction. Gastrointestinal duplication is a rare congenital abnormality found in adults. This intestinal duplication may be associated with complications i.e. perforation, bleeding, obstruction and malignancy. Degeneration to malignancy is a basic consideration to treat a radical surgery, which is preventive. This systematic review aims to provide evidences to evaluate the preventive or conservative surgery in the management. Method. A systematic review conducted according to preferred reporting items for systematic review and meta–analysis protocols (PRISMA). Literature search proceeded on PubMed and ScienceDirect using keywords "malignancy arising from adult duplication gastrointestinal "AND" treatment ". All articles are selected based on inclusion and exclusion criteria. The data evaluated included postoperative complications, recurrence, follow–up and recovery. Results. There were eleven articles – which were case reports – analyzed. These articles reported preventive surgery provide a better outcome than conservative one. Conclusion. Case reports in the study showed that 63% of intestinal duplication were developed to malignancy, requiring preventive surgery (level of evidence IV). However, this should be judge with a careful clinical assessment.